2009
DOI: 10.1080/02652030903045122
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of pesticide residues in fresh peach samples produced under integrated crop management in an agricultural region of northern Greece

Abstract: A multi-residue method using selected ion monitoring mode GC/MS has been developed for the quantitative analysis of residue levels of 23 widely used pesticides in fresh peaches produced under integrated crop management process (ICM). The proposed methodology involved a sample extraction procedure using liquidliquid partition with acetonitrile followed by a clean-up step based on solid-phase extraction (SPE). Fortification studies were performed at different concentration levels for various types of peaches tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 24 publications
(23 reference statements)
0
4
0
Order By: Relevance
“…The compounds investigated are mostly used on peach orchards in many parts of the world as recommended crop protection products. Researchers from different parts of the world have reported residues of the above-mentioned pesticides in peach samples (Zioris et al, 2009). Zioris et al (2009) reported 44.2% contamination of the analysed peach samples with chlorpyrifos at an average concentration of 0.036 mg/kg and 22.1% contamination with captan at an average concentration of 0.09 mg/kg, in Northern Greece.…”
Section: Real Samples Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The compounds investigated are mostly used on peach orchards in many parts of the world as recommended crop protection products. Researchers from different parts of the world have reported residues of the above-mentioned pesticides in peach samples (Zioris et al, 2009). Zioris et al (2009) reported 44.2% contamination of the analysed peach samples with chlorpyrifos at an average concentration of 0.036 mg/kg and 22.1% contamination with captan at an average concentration of 0.09 mg/kg, in Northern Greece.…”
Section: Real Samples Analysismentioning
confidence: 99%
“…Researchers from different parts of the world have reported residues of the above-mentioned pesticides in peach samples (Zioris et al, 2009). Zioris et al (2009) reported 44.2% contamination of the analysed peach samples with chlorpyrifos at an average concentration of 0.036 mg/kg and 22.1% contamination with captan at an average concentration of 0.09 mg/kg, in Northern Greece. Traces of endosulfan (0.004 mg/kg) and cypermethrin (0.031 mg/kg) were also reported in peach samples in Nawabshah, Sindh, Pakistan (Anwar et al, 2011).…”
Section: Real Samples Analysismentioning
confidence: 99%
“…A greater interest is provided for the most significant food matrices of the Greek production market such as olive oil, wine, honey, milk, vegetables, aquaculture products, etc. [ 139 , 140 , 141 , 142 , 143 , 144 , 145 ].…”
Section: Foodomicsgr_ri Plan and Strategymentioning
confidence: 99%
“…Fruit is important in the human diet and contains many nutrients, such as vitamins and minerals. Cherries, peaches, and kiwifruit are some of the most frequently consumed fruits and have remarkably high vitamin C, phenolic, anthocyanin, and flavonol contents. The production and consumption of cherries, peaches, and kiwifruit in China have increased in recent years. However, pesticides are commonly used during production of these fruits to control phytophages or pests that may damage the crops during growth, storage, or transport. Because of concerns about the potential effects of pesticides on fruit safety, many researchers have investigated pesticide residues in cherries, peaches, and kiwifruit and evaluated the health effects of detected residues on consumers. However, limited information is available regarding the residues of pesticide adjuvants in different fruits and especially about TSP n EOs in cherries, peaches, and kiwifruit.…”
Section: Introductionmentioning
confidence: 99%